Seroprevalence of SARS-CoV-2 infection among healthcare personnel in Gran Santa Fe (Argentina) during the COVID-19 pandemic - Nilva, Gabriela (2025)
Objective: To estimate the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection through antibody detection among healthcare personnel (HP) in Gran Santa Fe (Argentina) during virus sustained circulation and remission phases. Materials and methods: A longitudinal, population-based, seroepidemiological study was conducted. The target population consisted of HP working in second- and third-level public health centers in the Gran Santa Fe region. The sample comprised 600 active health workers, proportionally distributed across selected health centers. A self-administered questionnaire collected data on sociodemographic, occupational, clinical and exposure variables of interest. IgG and IgM antibodies to SARS-CoV-2 were detected from serum samples using indirect enzyme-linked immunoassays. Results: The prevalence of IgG antibodies to SARS-CoV-2 was 7.6 times higher during the virus circulation phase compared to the remission phase (2.1 % vs. 15.9 %, respectively), while no IgM antibodies were detected. Regarding the level of workplace exposure risk, the highest cumulative prevalence, 26.7 %, was observed in the high-risk group (workers in direct contact with patients and “assigned to the Intensive Care Unit [ICU]” or “assigned to the COVID-19 Area” or “assigned to the Emergency Department”). Nearly one-third of workers reported inconsistent use of recommended personal protective equipment (PPE), and fewer than 10 % reported full adherence to PPE guidelines, regardless of the level of exposure risk. The seroprevalence among HP who reported no symptoms since the beginning of the Aislamiento Social Preventivo y Obligatorio (Preventive and Mandatory Lockdown) was 12.3 % during the remission phase, compared to 10.0 % among HP with a history of negative RT-PCR results (p < 0.05). Conclusions: Complementing passive epidemiological surveillance with active serological surveillance using simple and cost-effective tests is important for accurately tailoring mitigation strategies in vulnerable populations such as HP.